2020
DOI: 10.30997/jsei.v6i1.2175
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Yang Mempengaruhi Profitabilitas Perbankan Syariah Di Indonesia

Abstract: Perbankan syariah di Indonesia telah menunjukkan trennya yang positif, bahkan lembagatersebut harus memiliki pondasi yang kuat untuk mempertahankan kemampuannya agardapat bersaing dengan perbankan syariah lainnya untuk mendapatkan profitabilitas yangdiharapkan. Kesuksesan tersebut dilihat dari banyak faktor salah satunya berdasarkanperforman perbankan syariah itu sendiri. Penelitian ini bertujuan untuk menganalisis NPF,FDR, CAR, dan BOPO sebagai variabel independen dan ROA sebagai variabel dependen. Jenispenel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The efficiency of banking asset management determines the level of profitability of an entity. Several studies have shown that during the COVID-19 pandemic, Islamic banking experienced a better profitability level compared to conventional (Fatmawati & Hakim, 2020;Tamimah, 2020;Wahyudi, 2020;Yanti & Maemunah, 2020). Also, the development of Islamic banking indicates that the preferences of the Indonesian people are increasingly leading towards sharia transactions.…”
Section: Islamic and Conventional Bankingmentioning
confidence: 99%
“…The efficiency of banking asset management determines the level of profitability of an entity. Several studies have shown that during the COVID-19 pandemic, Islamic banking experienced a better profitability level compared to conventional (Fatmawati & Hakim, 2020;Tamimah, 2020;Wahyudi, 2020;Yanti & Maemunah, 2020). Also, the development of Islamic banking indicates that the preferences of the Indonesian people are increasingly leading towards sharia transactions.…”
Section: Islamic and Conventional Bankingmentioning
confidence: 99%
“…This is contrary to the previous hypothesis, which states that FASBIS has a negative effect on inflation. This situation occurs because FASBIS has a relatively short time period, namely 1-14 days (Citra & Suman, 2022). Therefore, the impact of FASBIS as a liquidity-absorbing instrument was only visible at the beginning of this period.…”
Section: Figure 3 Irf Resultsmentioning
confidence: 99%